2001
DOI: 10.1021/jp010704a
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the Surface Crossing Process in Bacteriorhodopsin:  Computer Simulations of the Quantum Dynamics of the Primary Photochemical Event

Abstract: The quantum dynamics of the primary photoisomerization event in bacteriorhodopsin is studied by a semiclassical trajectory approach. The relevant surface crossing probability is evaluated from the wave functions and potential surfaces of a hybrid quantum mechanical/molecular mechanics (QM/MM) Hamiltonian of the complete chromophore-protein-solvent system. The QM/MM model combines consistently the quantum mechanical Hamiltonian of the chromophore with the microscopic electric field of the ionized groups and ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
189
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(203 citation statements)
references
References 86 publications
11
189
0
1
Order By: Relevance
“…Warshel et al (40) reported the first QM͞MM computation for an atomic-level model of bacteriorhodopsin (bR) using a QCFF͞PI Hamiltonian with the polarizable protein force field of the program ENZYMIX (40). An improved version of this method was used to model the bR excitation energy profile (11). After this initial effort, other QM treatments of the chromophore have been used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Warshel et al (40) reported the first QM͞MM computation for an atomic-level model of bacteriorhodopsin (bR) using a QCFF͞PI Hamiltonian with the polarizable protein force field of the program ENZYMIX (40). An improved version of this method was used to model the bR excitation energy profile (11). After this initial effort, other QM treatments of the chromophore have been used.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study (9), we implemented the ab initio CASPT2͞͞CASSCF protocol (where equilibrium geometries and electronic energies are determined at the CASSCF and CASPT2 levels, respectively) in a quantum mechanics͞ molecular mechanics (QM͞MM) scheme (10)(11)(12) allowing for the evaluation of the excitation energy of chromophores (treated quantum mechanically) embedded in a protein environment (described by a MM force field).…”
mentioning
confidence: 99%
“…Semiempirical approaches are promising in this regard [17]. The OM2 semiempirical Hamiltonian [18,19] with GUGA configuration interaction [20] is of particular interest because it has already been shown to give accurate absorption energies for bacteriorhodopsin [21] and to predict the spectral shift between bacteriorhodopsin and sensory rhodopsin II [22].…”
Section: Introductionmentioning
confidence: 99%
“…This protein colors the purple membrane of halobacteria and acts as a light-driven proton pump by means of a multistep process termed the photocycle (2). In the traditional model for the initial transduction step in this cycle is directly light-driven trans3cis isomerization of retinal (4)(5)(6); this model has been recently extended by including excited-state skeletal stretching (5,7). However, experiments with modified bR containing nonisomerizable retinal analogs challenged this model by showing that the initial photo-induced events are not associated with retinal isomerization (8)(9)(10).…”
mentioning
confidence: 99%